The Question of Religious Toleration in Spain in the Nineteeth Century - Bartlett, C. J. (The journal of ecclesiastical history, 1957)
Of all European states in the nineteenth century, Spain was among the slowest to respond to the great changes, social, political and economic, which were transforming Western civilisation. The Spaniard's reluctance to adopt the innovations of his neighbours, or to abandon the habits and outlook of a past age were a frequent source of friction between Spain and other nations; so much so that Lord Clarendon, whilst British foreign secretary, once likened Spain to a North African state with which Britain could have little in common on account of her failure to do ‘any of the many things which bind nations together’. Among the most persistent causes of dissension of this nature was the Spanish reluctance to tolerate the free practice of the protestant faith, and it is the object of this article to trace the gradual establishment of freedom of worship in Spain, and to estimate the respective contributions of the Spaniards themselves and of foreign pressure.